Critical Thinking Skills Analysis Students Studying Chemistry Using Problem Based Learning and Guided Inquiry Model - Muhammad Eka Putra Ramandha; Nurul Indriani (Jurnal Pendidikan dan Pembelajaran Kimia, 2021)
Abstract: Critical Thinking Skills Analysis Students Studying Chemistry Using Problem Based Learning and Guided Inquiry Model. The purpose of this study is to analyze the critical thinking skills of students. The independent variable is the guided inquiry learning model and the Problem Based Learning (PBL) model and the variable is critical thinking skills. The type of research used is a quasi-experimental design with a Non-equivalent Posttest Only Control Group design. 146 Students are subject in this study. Data collection was carried out with a description of 14 questions.  The results showed that the Critical Thinking Skills of students who were taught using the Problem Based Learning model was better than the guided inquiry learning model. Keywords: Guided Inquiry, Problem Based Learning (PBL), Higher Other Thinking Skills.  Abstrak: Analisis Keterampilan Berpikir Kritis Peserta Didik yang Belajar Kimia Menggunakan Model Pembelajaran Inquiry Terbimbing dan Model Pembelajaran Berbasis Masalah. Tujuan dalam penelitian ini yaitu untuk menganalisis keterampilan berpikir kritis peserta didik. Variabel bebasnya adalah Model Pembelajaran Inquiry terbimbing dan model pembelajaran PBL dan variabel terikatnya adalah keterampilan berpikir kritis. Jenis penelitian yang digunakan yaitu quasi eksperimen dengan desain Non-equivalen Posttest Only Control Group. Sampel dalam penelitian ini yaitu 146 peserta didik yang di tentukan dengan teknik Purposive sampling. Pengumpulan data dilakukan dengan soal tes uraian yang berjumlah 14 soal. Hasil Penelitian menunjukkan Keterampilan Berpikir Kritis (KtBK) peserta didik yang dibelajarkan dengan model PBL lebih baik dibandingkan dengan model pembelajaran inquiry terbimbing.Kata kunci: Inquiry Terbimbing, PBL, Keterampilan Berpikir KritisDOI: 10.23960/jppk. v10.i3.2021.16